2012
DOI: 10.1177/1477370812453103
|View full text |Cite
|
Sign up to set email alerts
|

Dealing with a gendered economy: Female drug dealers and street capital

Abstract: Early studies of female drug dealers suggest that women are marginalized, passive victims. In contrast, more recent studies describe women as skilful and competent dealers. In a Bourdieu-inspired theoretical framework of ‘street capital’, we suggest that the truth is somewhere in between. Female dealers can be successful, but they face more obstacles than men do. The illegal hard-drug economy is gendered and favours men. In this paper we discuss how female drug dealers develop particular strategies to prove th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
62
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(69 citation statements)
references
References 27 publications
4
62
0
3
Order By: Relevance
“…This finding echoes previous studies that have found that compared to their male counterparts, female IDU are more likely to rely on high risk income generation activities (DeBeck et al, 2007) and to experience higher unemployment (Richardson et al, 2010; McCoy et al, 2007; Pelissier & Jones, 2005). This earning disadvantage for female IDU may represent structural barriers that make it more difficult for female IDU to acquire high paying positions in both the legal labour market and shadow economies (Shannon et al, 2008; Pelissier & Jones, 2005; Grundetjern & Sandberg, 2012). Overall, these findings add to the empirical evidence supporting the need for interventions that provide economic empowerment, especially for female IDU (Deering et al, 2011; Richardson et al, 2010; DeBeck et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…This finding echoes previous studies that have found that compared to their male counterparts, female IDU are more likely to rely on high risk income generation activities (DeBeck et al, 2007) and to experience higher unemployment (Richardson et al, 2010; McCoy et al, 2007; Pelissier & Jones, 2005). This earning disadvantage for female IDU may represent structural barriers that make it more difficult for female IDU to acquire high paying positions in both the legal labour market and shadow economies (Shannon et al, 2008; Pelissier & Jones, 2005; Grundetjern & Sandberg, 2012). Overall, these findings add to the empirical evidence supporting the need for interventions that provide economic empowerment, especially for female IDU (Deering et al, 2011; Richardson et al, 2010; DeBeck et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Other successful women in drug economies enact typically masculine traits, particularly "street masculinity" (Grundetjern & Sandberg, 2012). These women claim that aggressive, tough, or masculine personas are necessary to gain access to and survive in certain criminal networks even when that means adopting male perceptions of women as weak and incapable (Brookman, Mullins, Bennett, & Wright, 2007;Miller, 1998).…”
Section: Women and Drug Economiesmentioning
confidence: 99%
“…Another way these dealers accomplished being viewed as one of the guys was through actively downplaying feminine bodily characteristics and abstaining from random sexual activity, previously referred to as desexualization (Grundetjern and Sandberg, ). Karen (36) explained how she responded to continuous sexual approaches by male colleagues.…”
Section: Findings and Analysismentioning
confidence: 99%